2014
DOI: 10.3346/jkms.2014.29.9.1205
|View full text |Cite
|
Sign up to set email alerts
|

Drug Survival Rates of Tumor Necrosis Factor Inhibitors in Patients with Rheumatoid Arthritis and Ankylosing Spondylitis

Abstract: We investigated the compliance of Korean patients using tumor necrosis factor (TNF) inhibitors to treat rheumatoid arthritis (RA) and ankylosing spondylitis (AS), and identified potential predictors associated with treatment discontinuation. The study population comprised 114 RA and 310 AS patients treated with TNF inhibitors at a single tertiary center for at least 1 yr from December 2002 to November 2011. Of the 114 RA patients, 64 (56.1%) discontinued their first TNF inhibitors with a mean duration of 18.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…However, patients may stop or switch their medications because of inefficacy, adverse reactions, and other issues such as insurance‐related problems. Lack of response to TNFi ranges between 30% and 55% of AS patients . In our study, among patients treated mainly for axial disease, 37% of the patients needed to stop or switch their TNFi because of treatment failure.…”
Section: Discussionmentioning
confidence: 70%
“…However, patients may stop or switch their medications because of inefficacy, adverse reactions, and other issues such as insurance‐related problems. Lack of response to TNFi ranges between 30% and 55% of AS patients . In our study, among patients treated mainly for axial disease, 37% of the patients needed to stop or switch their TNFi because of treatment failure.…”
Section: Discussionmentioning
confidence: 70%
“…Despite the benefits anti-TNF drugs have in the control of both diseases 14 , 17 , some patients experience therapeutic failure or go by adverse events and end up interrupting their therapies 10 . However, no studies have been conducted so far to analyze the use of these medications in the context of SUS.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from two Korean studies, 24,25 one Japanese prospective cohort study was identified that analyzed patients who started biologic treatment with infliximab, etanercept, or tocilizumab. 26 The authors found significant differences in demography, clinical status, comorbidities, and usage of concomitant drugs among the three drugs.…”
Section: Introductionmentioning
confidence: 99%
“…24,40 The regression results give rise to evidence (limited to the continuing population) that comorbidities increased the probability of treatment discontinuation, which is in line with international results. 21 Other studies, however, found that the CCI does not affect persistence, 9,25 and the indication of peptic ulcer disease even had a positive effect on persistence of tumor necrosis factor inhibitors. 25 According to our estimates, the elderly seem to be more persistent than younger patients.…”
mentioning
confidence: 97%
See 1 more Smart Citation